Pernikahan Poligami Tanpa Izin Pengadilan Agama dan Pengaruhnya Terhadap Kehidupan Rumah Tangga - Anggraeni Wijayanti, Dewi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper examines the problem of polygamy, namely the marriage of a husband with more than one woman. To be able to carry out a polygamous marriage, a husband must submit an application to the Religious Court with the reasons and conditions determined by Law number 1 of 1974 concerning marriage. However, in reality now marriage organizers in some communities are not in accordance with the rules of marriage law. Like the rampant practice of underhand polygamy, this marriage is carried out secretly or in secret. North Pekalongan. This research is a descriptive field research with data collection techniques used are interviews, observations which are a reference to analyze the results of the study. the polygamist feels that he is able to be fair to his wives without feeling for the first wife, but the reality does not match what is said. Their polygamous marriages are mostly carried out under the hands due to a lack of awareness and importance in recording marriages by reason of the complicated procedures set out by law, so they choose unregistered marriages as a way of marriage.